Air exposed 1, 4-bis(trimethylsilyl)-1, 4-dihydropyrazine: an avant-garde carbonization precursor for multi-functionalized carbon material. Issue 94 (13th November 2020) - Shoukat Ali, Shaikh Saddam; Roy, Kingshuk; Akula, Naveenkumar; Ogale, Satishchandra B.; Majumdar, Moumita
Abstract : 1, 4-Bis(trimethylsilyl)-1, 4-dihydropyrazine acts as a small molecule precursor for carbonization to multi-functionalized carbon via polymeric intermediate formation upon air exposure. Abstract : 1, 4-Bis(trimethysilyl)-1, 4-dihydropyrazine 1 has been utilized as a small molecule precursor for carbonization to N, O-containing few-layered carbon sheets 3 via the formation of a polymeric material 2 upon simple air exposure at room temperature. Without any further purification, this multi-functionalized carbon material 3 exhibited excellent anode performance in a lithium ion battery.